Biology Contributions Biological equivalence between LDR and PDR in cervical cancer: multifactor analysis usingthe linear-quadratic model - Couto, José Guilherme; Pirraco, Rui; Bravo, Isabel (Journal of Contemporary Brachytherapy, 2011)
Purpose: The purpose of this work was the biological comparison between Low Dose Rate (LDR) and Pulsed Dose Rate (PDR) in cervical cancer regarding the discontinuation of the afterloading system used for the LDR treatments at our Institution since December 2009. Material and methods : In the first phase we studied the influence of the pulse dose and the pulse time in the biological equivalence between LDR and PDR treatments using the Linear Quadratic Model (LQM). In the second phase, the equivalent dose in 2 Gy/fraction (EQD2) for the tumor, rectum and bladder in treatments performed with both techniques was evaluated and statistically compared. All evaluated patients had stage IIB cervical cancer and were treated with External Beam Radiotherapy (EBRT) plus two Brachytherapy (BT) applications. Data were collected from 48 patients (26 patients treated with LDR and 22 patients with PDR). Results : In the analyses of the influence of PDR parameters in the biological equivalence between LDR and PDR treatments (Phase 1), it was calculated that if the pulse dose in PDR was kept equal to the LDR dose rate, a small the-rapeutic loss was expected. If the pulse dose was decreased, the therapeutic window became larger, but a correction in the prescribed dose was necessary. In PDR schemes with 1 hour interval between pulses, the pulse time did not influence significantly the equivalent dose. In the comparison between the groups treated with LDR and PDR (Phase 2) we concluded that they were not equivalent, because in the PDR group the total EQD2 for the tumor, rectum and bladder was smaller than in the LDR group; the LQM estimated that a correction in the prescribed dose of 6% to 10% was ne-cessary to avoid therapeutic loss. Conclusions : A correction in the prescribed dose was necessary; this correction should be achieved by calculating the PDR dose equivalent to the desired LDR total dose.